The role of cholecalciferol deficiency in the development of dermatoses in geriatric patients - Anna V. Urakova; Yuri N. Perlamutrov; Dina E. Klyuchnikova (Consilium Medicum)
Background. Dermatological pathology, which includes a wide range of nosologies, is a common problem in geriatric patients. Currently, more and more attention is being paid to the importance of cholecalciferol deficiency in the pathogenesis of dermatoses, especially among the elderly. Vitamin D3 is known for its ability to modulate immune responses and perform many functions at the cellular level, including influencing the proliferation and differentiation of keratinocytes. Given the inevitable age-related changes in vitamin D3 metabolism and the increasing prevalence of dermatoses among geriatric patients, the present study aims to analyze the role of cholecalciferol deficiency on the course of dermatoses in this category of people.